Poetry Training for Tunas Harapan TK Students Using the Picture and Picture Method - Dardanila; Mulyadi; Susilo, Hariadi; Sembiring, Sugihana; Kudadiri, Amhar; Marsella, Emma (Talenta Publisher, 2023)
This training aims to train students speaking abilities and skills at Kindergarten Tunas Harapan Binjai. Poetry training from an early age hones the ability to think imaginatively, interest in reading, courage to express thoughts and feelings from the sensory process through the five senses in an image. Training was carried out in four sessions. In the first session, counseling was carried out and poetry material was delivered by the service team. The second session, training participants were asked to see and explain pictures using the five senses. The third session, Tunas Harapan Kindergarten students composed a poem by presenting pictures. The fourth session, Tunas Harapan Kindergarten students performed poetry in front of other participants and trainers, namely the service team, who gave feedback to Tunas Harapan Kindergarten students. After all participants appeared, a competition was held between participants and then the best participants I, II and III were selected. The results of this poetry training are: (1) Training from an early age the thinking and imagination skills of Tunas Harapan Kindergarten students in poetry. (2) Training Tunas Harapan Kindergarten students' interest and talent in poetry from an early age. (3) Providing intensive poetry training for Tunas Harapan Kindergarten students.